“Medicine food homology” plants promote periodontal health: antimicrobial, anti-inflammatory, and inhibition of bone resorption - Qu, Shanlin; Yu, Shuo; Ma, Xiaolin; Wang, Rui (Frontiers in Nutrition, 2023)
"Medicine food homology" (MFH) is a term with a lengthy history. It refers to the fact that a lot of traditional natural products have both culinary and therapeutic benefits. The antibacterial, anti-inflammatory and anticancer effects of MFH plants and their secondary metabolites have been confirmed by numerous research. A bacterially generated inflammatory illness with a complicated pathophysiology, periodontitis causes the loss of the teeth's supporting tissues. Several MFH plants have recently been shown to have the ability to prevent and treat periodontitis, which is exhibited by blocking the disease's pathogens and the virulence factors that go along with them, lowering the host's inflammatory reactions and halting the loss of alveolar bone. To give a theoretical foundation for the creation of functional foods, oral care products and adjuvant therapies, this review has especially explored the potential medicinal benefit of MFH plants and their secondary metabolites in the prevention and treatment of periodontitis.